BIOLOGICAL ACTIVITY AND THERAPEUTIC PROPERTIES OF PUNICA GRANATUM L - Bilovol, O.M.; Kniazkova, I.I.; Barbashova, V.O.; Kuzminova, N.V.; Mishchenko, V.K.; Kryvoshapka, O.V.; Abramova, L.P. (World of Medicine and Biology, 2025)
The purpose of the study was to summarize the literature on the phytochemistry of the main molecular mechanisms of action and pharmacological properties of Punica granatum L, as well as the results of experimental and clinical studies of its use in clinical medicine. Punica granatum L. has been used for centuries in traditional medicine in the world to prevent and treat a wide range of health disorders. The pomegranate fruit is an important source of nutrients, including dietary fiber, polysaccharides, vitamins, fatty acids, and polyphenols. Biologically active compounds of Punica granatum L. provide a powerful potential and a wide spectrum of biological and pharmacological activity. The peel, seeds, and juice of pomegranate contain significant amounts of phenolic compounds and have antioxidant activity. It was found that pomegranate extract showed significant antibacterial (mainly bactericidal), antifungal effects and antiviral properties. Polyphenols such as punicalin, punicalagin, and ellagic acid are just some of the many compounds responsible for the anticancer activity of pomegranate. Punica granatum L. and its derivatives, such as ellagic acid, can regulate the expression and activity of several molecular targets related to oxidative stress, inflammation, cell cycle, apoptosis, angiogenesis, invasion, and metastasis, which makes it promising for further research in various pathological conditions.